On Comparison of Crisp, Fuzzy, Intuitionistic Fuzzy Unconstrained Optimization Problems Using Newton’s Method - Hepzibah, R. Irene; Emimal, S. Shilpa Ivin (Communications in Mathematics and Applications, 2022)
This paper is focused on arithmetic operations on fuzzy and intuitionistic fuzzy numbers to solve the fuzzy unconstrained optimization problems with triangular and trapezoidal, fuzzy number coefficients. The optimal solution is obtained by fuzzy Newton’s method, and the MATLAB outputs are also provided with illustrative examples. The method proposed in this research work has been compared with the existing Newton’s method.
Keywords: Complex interval-valued Pythagorean fuzzy set; Fuzzy numbers; Intuitionistic set; Unconstrained optimization